The military government, nature, and agricultural frontier in the Brazilian Midwest (1964-1979) (Research, Society and Development, 2022)
The article aims to identify through the analysis of public policies and environmental laws (1964-1979) if the Brazilian State helped the agricultural frontier expansion in the Brazilian Midwest. It was made a narrative review, based in search in the database: Capes Periodical, Capes Theses and Dissertations Catalog, Google Scholar, and Mendeley as a reference manager. Also, there were consulted the sites of the Legislative Panel of the Environment Ministry for environmental laws analysis. And for Public Policies analysis: Database of Foundation Getúlio Vargas, Center for Research and Documentation of Contemporary History of Brazil, Brazilian Institute of Geography and Statistics. The results demonstrate that the military government during the period under analysis contributed, through the publication of public policies and environmental laws, for the expansion of the agricultural frontier in the Midwest.